2004
DOI: 10.1063/1.1827920
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surface waviness in thin films via volume and surface diffusion

Abstract: Deformation mechanisms involving mass transport by stress driven diffusion influence a large number of technological problems. We study the formation of undulations on surfaces of stressed films at high temperature by exploring the deformation kinetics governed by volume and surface diffusion. A governing equation is derived that gives the amplitude change of such surfaces as a function of time. A parametric study is then carried out using a range of practically important input values of the film material prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 40 publications
0
28
0
4
Order By: Relevance
“…The influence of external strain fields on atomic mobility have has been observed in both simulations and experiments [1][2][3][4][5][6][7][8] . This coupling between the strain-field and atomic migration barriers has been well recognized in a variety of surface processes, e.g., selfassembly of nano-clusters, growth of thin films, surface instabilities, etc.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The influence of external strain fields on atomic mobility have has been observed in both simulations and experiments [1][2][3][4][5][6][7][8] . This coupling between the strain-field and atomic migration barriers has been well recognized in a variety of surface processes, e.g., selfassembly of nano-clusters, growth of thin films, surface instabilities, etc.…”
Section: Introductionmentioning
confidence: 88%
“…For instance, Zhu et al reported kinetic Monte-Carlo simulations on the effects of surface strain on the growth of quantum dots 5 . Panat et al also studied the evolution of surface waviness modulated by surface strain 6 . These studies show that it is necessary to have a full understanding of the effects of the surface stress state on atomic diffusion in order to build up comprehensive models that describe the dynamics of surface evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Including this effect in the surface dynamics gives rise to a term ϰM͉q͉ 3 on the RHS of Eq. ͑31͒, 53 where M ϰ 0 2 . This term does not stem from local effects but rather from nonlocal effects associated with reducing elastic energy throughout the whole solid.…”
Section: B Asaro-tiller Mechanismmentioning
confidence: 99%
“…The QD composition is determined by the intermixing during the dot formation due to mass transfer along the wetting layer. [15][16][17] The interfaces of QDs being independent on their composition are given by stable crystallographic planes, which ensure minimization of the interface energy. These planes provide interface stability against the intermixing with the matrix material during the overgrowth of the QDs.…”
mentioning
confidence: 99%